APLIKASI NILAI-NILAI ISLAM DALAM PERATURAN DAERAH (PERDA) TENTANG PENGELOLAAN ZAKAT DAN PROBLEMATIKANYA PADA ERA OTONOMI DAERAH DI KOTA SEMARANG - Ira Alia Maerani (Unissula, 2012)
Zakat is an obligation for Muslims who associated with property owned by someone. It has tremendous potential for alleviating poverty. According to data Bappeda of Semarang, the number for poor people in the year 2008 reached 498,700 people or 31 % of the total population of the city of Semarang. This thesis raised two formulations of the problem. They are how the application of Islamic values in Local Zakat Management and what the problems and the solutions in the application of Islamic values against the Law Zakat Management in the era of regional autonomy in the city of Semarang.Application of Islamic values in the management of zakat as the values into the divinity (Tawheed), humanity, brotherhood, responsibility, and justice. Islamic values are already visible in our country basis of Pancasila. Islamic values are also contained in the Regional Regulation (Perda) Number 7 of 2009 on Management of Zakat. But the application of Islamic values is still weak. Normative problem faced is the lack of the punishments for the Muzakki who is ungrateful to pay zakat. The absence of sanctions to make products of this law (Law No. 38 of 1999 and Regional Regulation No. 7 of 2009) can not be said to be a law. As John Austin says there are four important elements to be named as the law, ie: commands, punishments, obligations, and sovereignty.Keywords: Application, Values of Islam, Regional Regulation, Zakat Management.